Biological significance of soluble IL-2 receptor - Calogero Caruso; Giuseppina Candore; Diego Cigna; Antonio Tobia Colucci; Maria Assunta Modica (Mediators of Inflammation)
A NUMBER of receptors for growth factors and differentiation antigens have been found to be secreted or released by cells. Following mononuclear cell (MNC) activation and interleukin-2 receptor (IL-2R) expression, a soluble form of the Alpha;-chain of IL-2R (sIL-2R) is released. The sIL-2R has been shown to be present in the culture supernatants of activated MNCs as well as in normal sera and, in higher amounts, in sera from subjects affected by several diseases including neoplastic, infectious and autoimmune ones, and in sera from transplanted patients suffering allograft rejection. The blood sIL-2R levels depend on the number of producing cells and the number of molecules per cell, so that sIL-2R blood values may represent an index of the number and the functional state of producing cells, both normal and neoplastic. Thus, monitoring of the immune system, mostly T-cells and haematological malignancies might be targets for the measurement of sIL-2R. Since many conditions may influence sIL-2R production, little diagnostic use may result from these measurements. However, since blood sIL-2R levels may correlate with disease progression and/or response to therapy, their measurement may be a useful index of activity and extent of disease. The precise biological role of the soluble form of the IL-2R is still a matter of debate. However, we know that increased sIL-2R levels may be observed in association with several immunological abnormalities and that sIL-2R is able to bind IL-2. It is conceivable then that in these conditions the excess sIL-2R released in vivo by activated lymphoid cells or by neoplastic cells may somehow regulate IL-2-dependent processes. On the other hand, it cannot exclude that sIL-2R is a by-product without biological significance. Finally, it is puzzling that in many conditions in which an increase of blood sIL-2R values has been observed, MNCs display a decreased in vitro capacity to produce sIL-2R. These seemingly contrasting findings are discussed in the light of the data showing that sIL-2R production correlates with IL-2 production.